Evaluation Conducted With University Teachers on the General Physics Courses Taught at the National University of Costa Rica During 2014 and 2019 - Márquez-Artavia, Xiomara; Delgado-Orozco, Luis; Saavedra-Arias, José (Revista Electrónica Educare, 2022)
Objective. Evaluate the General Physics courses (theory and laboratory) of the Science Teaching career with the university teaching staff, in the period from 2014 to 2019, to identify the strengths and weaknesses in the methodology and propose new educational strategies. Method. The research was conducted through a virtual survey with the LimeSurvey software to the teachers who have taught Physics courses for the Science Teaching career in the last five years; the survey was applied to the total population of 20 teachers, but only 12 of them answered it. The instrument was designed by the teaching staff working on the project to improve the laboratory manuals. The instrument analysis was carried out with the help of an Excel spreadsheet provided by the LimeSurvey software. The instrument was validated by IDESPO staff of the National University regarding the relevance of the content of the statements, the clarity of the questions, and the coherence with the objective of this study. Results. The structure and organization of the General Physics courses have a positive assessment by the teachers, who also showed a preference for the traditional lecturing; but even so, they are willing to train and learn new teaching strategies. Conclusions. The results of this investigation show that teachers are open to technological change and to working on the challenges that government policies have proposed.